2018
DOI: 10.2174/1871520618666180507130243
|View full text |Cite
|
Sign up to set email alerts
|

Cold Physical Plasma-Treated Buffered Saline Solution as Effective Agent Against Pancreatic Cancer Cells

Abstract: Plasma-treated PBS inhibited cell growth in 2D and 3D models of cancer. These results may help facilitate the development of new plasma-derived anticancer agent with clinical relevance in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies by others and us have observed plasma-induced tumor cell death before [82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Kumar and colleagues observed in several pancreatic cancer cell lines an increase in apoptosis concomitant with downregulation of MAPK7, BCL2, and CHK1 [99].…”
Section: Discussionmentioning
confidence: 94%
“…[ 106 ] Besides the ICD‐inducing nature of plasma‐mediated tumor cell death shown in our present work, gas plasma treatment but not a positive control failed to induce autoimmune events in a previous study in vivo [ 107 ] that would have occurred in case of an overshooting immune reaction after plasma exposure. In addition, we recently established tumor‐toxic gas plasma treatment [ 108 ] to be void of pro‐metastatic effects in four human pancreatic cancer cell lines. [ 109 ]…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of investigations on plasmaliquid interactions has demonstrated the occurrence of ROS and RNS in liquid phases following plasma treatment (36,37). Moreover, it has been shown several times that liquids, such as water, physiological saline, or cell culture media become biologically effective following plasma treatment (100)(101)(102)(103)(104)(105). This underlines a key role of liquid phase composition for biological plasma effects.…”
Section: Redox Biology As the Scientific Grounding Of Plasma Medicinementioning
confidence: 99%